2021
DOI: 10.1186/s41927-021-00226-y
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of e-learning in patient education delivered to patients with rheumatoid arthritis: The WebRA study—protocol for a pragmatic randomised controlled trial

Abstract: Background Patient education is integral to the treatment and care of patients with rheumatoid arthritis. Change is taking place in the organisation of healthcare systems because of a demographic shift towards ageing populations, an increasing use of technology and advancements in digital technologies, allowing for new interventions. This study will aim to evaluate the effectiveness of a newly developed e-learning patient education programme based on self-management that targets patients with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Especially newly diagnosed patients are facing a lot of distress and new questions [ 8 , 9 ]. Furthermore, patients with established diagnosis [ 10 ] are confronted with questions regarding management of disease flares, infections or medication side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Especially newly diagnosed patients are facing a lot of distress and new questions [ 8 , 9 ]. Furthermore, patients with established diagnosis [ 10 ] are confronted with questions regarding management of disease flares, infections or medication side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis, a condition caused by an immune reaction in which the body attacks itself after mixing up its own tissues with foreign chemicals, affects 20 million individuals worldwide. This condition, roughness in the joints, and possible organ inflammation are all brought on by the illness [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, emphasized that educational needs may differ from one individual to another and may change over the course of the disease. It is recommended that patient education should begin immediately after the patient has been diagnosed or as early as possible; it also should be individually tailored and should address different aspects of the disease [3]. It has also been shown that patients need knowledge in order to exercise appropriate behavior and practices to manage their symptoms and complaints associated with their disease.…”
Section: Formation Of Attitudes and Behaviors As Part Of Coping With ...mentioning
confidence: 99%
“…The need for patient education is widely recognized [1]. It is an important aspect of nursing care that would allow patients to manage their disease and improve their health outcomes [2], thus maintaining a better quality of life (QoL) [3].…”
Section: Introductionmentioning
confidence: 99%